Breaking New Ground In Human Rights Protection: Proposing An Inverted Triangular Approach Through Group-Based Enforcement In South East Asia - Shahrul Mizan Ismail (Jember University Press, 2017)
The present problem of human rights enforcement reflects the old dilemma between centralism at the international level and local governance at the domestic level. Centralist solutions carry the expectation of a more homogeneous, effective and uniform method of operation. But this so-called‘universal’enforcement model is often seen as being too weak and incoherent for effective actions.Although the alleged universal character of the enforcement of human rights may portray an impressive international regime, local modes of problem solving are in reality more efficient since they are based on a better understanding of the specific circumstances and take into account of local peculiarities, cultural values and other similar factors. The latter is the missing elements in the overall international human rights enterprise. The rapid promotion and education of the global community on the concept of human rights has opened many wider possibilities for group based enforcement to be an efficient alternative. Reinforcing the same line of argumentation, this paper proposes an inverted model of enforcement whereby iinternational human rights law could act as the general framework that establishes generally agreed principles and norms that transcend strict national concerns, while group based mechanisms will work on enforcing those norms in their specific manifestations within the respective groups.